Insights gained from two decades of intensive monitoring: hydrology and nitrate export in a tile-drained agricultural catchment - Bauwe, Andreas; Lennartz, Bernd (Frontiers in Water, 2024)
Nitrate (NO3-) export from agricultural land poses an ongoing threat to both inland and coastal waters. Experimental studies investigating the hydrology-NO3–export mechanisms require long-term data to identify reliable causal relationships. In this study, utilizing a 23-year continuous dataset with a high temporal resolution (daily to twice a week), we aim to identify potential drivers for NO3- losses and assess the impact of nitrogen (N) soil surface budgets on NO3- export. A drainage plot (4.2 ha) and a ditch catchment (179 ha) were fully equipped to register hydrological parameters, including water sample collection. Mean annual NO3–N concentrations (loads) for the drainage plot and the ditch catchment were 9.4 mg l⁻¹ (20.6 kg ha⁻¹) and 6.0 mg l⁻¹ (20.9 kg ha⁻¹), respectively. Annual discharge was closely positively correlated with annual NO3- losses, highlighting the significant influence of prevailing weather and, consequently, hydrologic conditions on NO3- export rates. The majority of the annual NO3–load was exported during winter (56% at the drainage plot, 51% at the ditch catchment), while the rest was exported during spring (28%, 29%), summer (9%, 9%) and fall (7%, 11%). We could not find any direct relationships between N soil surface budgets and NO3- losses. Putting all results together, it can be concluded that agricultural activities for many decades resulted in high soil N stocks, which determined the general high NO3–N concentration levels. Nevertheless, temporal NO3- export dynamics during the last two decades were clearly driven by hydro-meteorological conditions, nearly independently of land management and N soil surface budgets on the fields.